Effects of Alhagi camelorum Fisch polysaccharide from different regions on growth performance and gastrointestinal microbiota of sheep lambs - Manafu, Zulikeyan; Zhang, Zhenping; Malajiang, Xieraili; Abula, Saifuding; Guo, Qingyong; Wu, Yi; Wusiman, Adelijaing; Bake, Batur (Frontiers in Pharmacology, 2024)
Polysaccharides derived from Alhagi camelorum Fisch possess diverse activities, making them a potential prebiotic candidates for enhancing lamb health. This study investigated the immunomodulatory effects of Alhagi camelorum Fisch polysaccharides from Aksu (AK) and Shanshan (SS) regions on sheep lambs. The results showed that sheep lambs in the SS group exhibited significantly increased (P < 0.05) average daily gain, levels of growth hormone (GH), insulin (INS), IgA and IgM, and cytokines IL-4, IL-10, IL-17, TNF-α and IFN-γ compared to those in the control check (CK) group. Moreover, the SS treatment significantly increased the diversity and abundance of beneficial bacteria, while concurrently diminishing the prevalence of harmful bacteria. Additionally, it modulated various metabolic pathways, promoted lamb growth, improved immunity, reduced the risk of gastrointestinal disease and improved the composition of gastrointestinal microbiota. In summary, our findings highlight the potential of SS treatment in enhancing gastrointestinal health of sheep lambs by improving intestinal function, immunity, and gut microbiome. Consequently, these results suggest that Alhagi camelorum Fisch polysaccharides derived from Shanshan regions holds promising potential as a valuable intervention for optimizing growth performance in sheep lambs.